2018
DOI: 10.1016/j.catcom.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Dry reforming of methane over Zr- and Y-modified Ni/Mg/Al double-layered hydroxides

Abstract: Zr-and Y-promoted Ni/Mg/Al double-layered hydroxides were investigated in dry reforming of methane, DRM (10% CH4, CH4/CO2=1, GHSV=20,000 h-1) for the first time. Modification of the double-layered hydroxides with 5 wt% of zirconium and 0.4 wt% of yttrium resulted in the formation of ZrO2-Y2O3 solid solution, which largely contributed to the enhancement of catalyst's stability with time-on-stream at 700 °C in DRM. Also, the modified catalyst demonstrated the limitation of the reverse WGS reaction, as confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 43 publications
7
31
0
Order By: Relevance
“…Similar positive effects were reported in other Y-promoted materials tested in DRM [18,[23][24][25][26]. Moreover, Zr-modified hydrotalcites doped with yttrium (0.2-0.6 wt.%) showed good catalytic performance [18]. In this study, the promotion with 0.4 wt.% of Y led to the better activity and stability (as compared to the Y-free material) that was linked to the formation of solid solution of ZrO 2 -Y 2 O 3 , which enhanced reduction of bulk NiO.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar positive effects were reported in other Y-promoted materials tested in DRM [18,[23][24][25][26]. Moreover, Zr-modified hydrotalcites doped with yttrium (0.2-0.6 wt.%) showed good catalytic performance [18]. In this study, the promotion with 0.4 wt.% of Y led to the better activity and stability (as compared to the Y-free material) that was linked to the formation of solid solution of ZrO 2 -Y 2 O 3 , which enhanced reduction of bulk NiO.…”
Section: Introductionsupporting
confidence: 87%
“…In our previous study we showed that Y (0.6-1.5 wt.%) increased specific surface area of Ni-DLHs, led to smaller Ni crystallites and enhanced dispersion of active sites as compared to the unpromoted catalyst [4]. Similar positive effects were reported in other Y-promoted materials tested in DRM [18,[23][24][25][26]. Moreover, Zr-modified hydrotalcites doped with yttrium (0.2-0.6 wt.%) showed good catalytic performance [18].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…As we recently reviewed, the nature of the support has a strong influence on the activity, selectivity and stability of supported Ni catalysts in DRM reaction . Support materials such as SiO 2 , KCC‐1, KIT‐6, Al 2 O 3 , CeO 2 , perovskites and zeolites have been investigated in DRM. In general, zeolites are microporous crystalline aluminosilicates.…”
Section: Introductionmentioning
confidence: 99%